A new species of Stegopterna Enderlein, and its relationship to the allotriploid species St. mutata (Malloch, 1914) (Diptera: Simuliidae) - Currie, Douglas C.; Hunter, Fiona F. (Zootaxa, 2003)
A new species of black fly, Stegopterna diplomutata n. sp. (Diptera: Simuliidae) is described and illustrated. This species is most closely related to Stegopterna mutata (Malloch, 1914), with which it has long been confused. The two species are most easily distinguished based on the presence or absence of males; St. diplomutata is a diploid bisexual species that possesses males, whereas St. mutata is a triploid parthenogenetic species that lacks males. The two species are otherwise not distinguishable except through examination of their larval polytene chromosomes. Observations are provided about the evolution of triploidy in Stegopterna.